Endothelial chimerism in chronic sclerotic‐type chronic graft‐versus‐host disease (GVHD) and GVHD‐associated angiomatosis. (1st October 2016) - Kaffenberger, B.H.; Zhang, E.; Duncan, J.R.; Jaglowski, S.; Klisovic, R.B.; Devine, S.M.; Wong, H.K.; Gru, A.A.
Summary: Graft‐versus‐host disease‐associated angiomatosis (GVHD‐AA) is an uncommon manifestation of chronic GVHD consisting of friable vascular proliferations. Using fluorescence in situ hybridization, we demonstrate the presence of donor‐derived endothelial cells within areas of GVHD‐AA. This is the first documented occurrence of a benign neoplastic growth in relationship to a form of chronic GVHD.